N-Doped Graphene from Metal-Organic Frameworks for Catalytic Oxidation of p-Hydroxylbenzoic Acid: N-Functionality and Mechanism - Liang, P.; Zhang, C.; Duan, Xiaoguang; Sun, Hongqi; Liu, Shaomin; Tade, Moses; Wang, Shaobin (American Chemical Society, 2017)
© 2017 American Chemical Society.N-doped graphene has been considered as a promising catalyst with surface metal-free active sites for environmental remediation. Several MIL-100 (Fe)-templated N-doped graphene samples were synthesized using dicyandiamide, melamine, and urea as the nitrogen precursors. Excellent catalytic oxidation of p-hydroxylbenzoic acid (PHBA) was observed on the as-synthesized samples via peroxymonosulfate (PMS) activation. The mechanism was investigated by both electron paramagnetic resonance (EPR, 5,5-dimethyl-1-pyrroline N-oxide and 2,2,6,6-tetramethyl-4-piperidinol as the trapping agents) and quenching tests (ethanol and sodium azide as the radical scavengers). Benzoic acid and furfuryl alcohol were also employed as probing reagents for hydroxyl/sulfate radicals and singlet oxygen, respectively. The results confirmed that singlet oxygen was generated and dominated the PHBA degradation on N-doped graphene, rather than hydroxyl/sulfate radicals. With the novel N-doped graphene, this study illustrates the formation mechanism of nitrogen functionalities for reactive radicals via PMS activation for removal of organic contaminants in water.